Peran Orang Tua Dalam Pengawasan Penggunaan Smart Phone Pada Anak Usia Dini - Isyuliani; Syamsudin; Budiman (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2024)
This research is a type of qualitative descriptive research with a case study approach. The purpose of this study was to determine the Role of Parents in Smart Phone Supervision in Early Childhood. This study focuses on the problem of how the role of parents in preventing addictive behavior of playing Smart Phone in Early Childhood at KB. Mutiara Hati. This research data collection uses observation and interviews. The results of research that has been conducted by researchers, the Role of Parents in Smart Phone Supervision in Early Childhood, among others: 1) the role of parents interacting with children, 2) control in the use of Smart Phones in children, 3) parents must be firm and disciplined, 4) increase children's activities / invite children to play outside.